Changes in Parental Hopes for Seriously Ill Children - Hill, Douglas L. (Pediatrics, 2018)
BACKGROUND: Hopes of parents of children with serious illness play an important role in decision-making and coping. Little is known about how parent hopes change over time. We describe the changes in parent hopes across multiple domains and time intervals, examine hopes in a subgroup of parents whose child died, and explore the maintenance of domains over time. METHODS: In a mixed-methods prospective cohort study on decision-making, parents of seriously ill children reported demographic characteristics and hopes at baseline and reported any changes in hopes at 4-, 8-, 12-, 16-, and 20-month follow-up visits. Hopes were coded into 9 domains. Hope changes and domain changes were identified for each parent at each visit. RESULTS: One hundred and ninety-nine parents of 158 patients most often reported hopes in the domains of quality of life (75%), physical body (69%), future well-being (47%), and medical care (34%). Hope percentages increased over time for quality of life (84%), future well-being (64%), and broader meaning (21%). The hope domains reported by parents of children who died were similar to the rest of the sample. The majority of parents who completed 5 to 6 follow-up visits changed at least 1 domain. At the individual parent level, some domains revealed considerable change over time, whereas other domains were stable among a subset of parents. CONCLUSIONS: The specific hopes and overall areas of hope of parents of seriously ill children vary over time, although most hopes fall within 4 major areas. Accordingly, clinicians should regularly check with parents about their current hopes.